Adam Smith economic morals - De Dios, Emmanuel S. (University of the Philippines, 2006)
This lecture tackles about Adam Smith who shape the discourse of what we call economics. The discussion is divided in three parts such as: Brief introduction of Adam Smith's moral philosophy; discussion of book proper in economics entitled Wreath of the Nations; Remarks on the successes of Adam Smith.